Higiene e recreação: parques infantis de São Paulo, 1935-1938 - Grindler, Victor (2015)
The present study analyzes topics of public health interest at a time when new ideas in this field were developed in São Paulo, using the children s playgrounds, in the period from 1935 to 1938, as study case. The hypothesis underpinning this study is that within the Brazilian public health setting in the 1930s, public spaces, like the children s playgrounds, provided the scenario for actions aiming at the prevention of disease and promotion of health. Three different agendas could be identified as underlying the establishment of children s playgrounds in São Paulo: the one by the group around Paulo Duarte and Mário de Andrade pursued cultural and national identity interests. The second was prominently concerned with hygienic matters and corresponded to the ideals of the so-called Paula Souza Reform . Finally, the third agenda was the one of Nicanor Miranda, the director of the Division of Education and Recreation, which was based on a new and broad-scoped concept of physical education